2014
DOI: 10.1111/imm.12243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PDL1 cross‐linking on cell death in PDL1‐expressing cell lines and bovine lymphocytes

Abstract: SummaryProgrammed death-ligand 1 (PD-L1) blockade is accepted as a novel strategy for the reactivation of exhausted T cells that express programmed death-1 (PD-1). However, the mechanism of PD-L1-mediated inhibitory signalling after PD-L1 cross-linking by anti-PD-L1 monoclonal antibody indicating that PD-1-Ig-induced immunosuppression in bovine lymphocytes could be caused by PD-L1-mediated B-cell death. This study provides novel information for the understanding of signalling through PD-L1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 37 publications
1
68
0
Order By: Relevance
“…PBMCs, splenocytes, and lymphocytes were isolated from tissues and were then blocked with PBS containing 10% goat serum and washed and stained with MAbs against PD-L1:4G12 (rat IgG2a [20]) and CD11b:CC126 (mouse IgG2b; AbD Serotec) for 30 min at room temperature. After a washing step with PBS containing 10% goat serum, the cells were stained with CD14-APC/ Cy7:CAM36A (VMRD), MHC-II:CAT82A (VMRD) prelabeled with Zenon R-PE mouse IgG1 labeling kit (Life Technologies, Carlsbad, CA), APC-conjugated anti-rat immunoglobulin (Beckman Coulter), and fluorescein isothiocyanate (FITC)-conjugated anti-mouse IgG2b (Beckman Coulter) antibody conjugates for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMCs, splenocytes, and lymphocytes were isolated from tissues and were then blocked with PBS containing 10% goat serum and washed and stained with MAbs against PD-L1:4G12 (rat IgG2a [20]) and CD11b:CC126 (mouse IgG2b; AbD Serotec) for 30 min at room temperature. After a washing step with PBS containing 10% goat serum, the cells were stained with CD14-APC/ Cy7:CAM36A (VMRD), MHC-II:CAT82A (VMRD) prelabeled with Zenon R-PE mouse IgG1 labeling kit (Life Technologies, Carlsbad, CA), APC-conjugated anti-rat immunoglobulin (Beckman Coulter), and fluorescein isothiocyanate (FITC)-conjugated anti-mouse IgG2b (Beckman Coulter) antibody conjugates for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether immunoinhibitory receptors influence M. avium subsp. paratuberculosis-specific IFN-␥ responses, heparinized whole blood cells were incubated with the blocking MAb anti-PD-1:5D2 (13), anti-PD-L1: 5A2 (20), or anti-LAG-3:71-2D8 (the present study) at 10 g/ml, and rat IgG (Sigma-Aldrich) was used as a negative-control antibody in the presence of 5 g of J-PPD/ml. For negative-control antigen, PPD was purified from the Mycobacterium bovis BCG strain (B-PPD; 5 g/ml), or sterile PBS was used.…”
Section: Methodsmentioning
confidence: 99%
“…Antibody blockade assays. To examine the effects of blocking MAbs on OM-specific T-cell responses, in vitro blockade assays were performed by using PBMCs cultured in complete RPMI 1640 medium with 10 g/ml of the blocking MAbs anti-PD-L1 (4G12) (16) and anti-LAG-3 (71-2D8) (14) or control rat IgG (Sigma-Aldrich) in the presence of 0.2 g/ml of OMs. The same amount of uRBCs was used as a negative-control antigen.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on chronic infections of cattle revealed that the upregulation of bovine PD-1 and LAG-3 in T cells was closely associated with the exhaustion of T-cell responses and disease progression during bovine leukemia virus (BLV) infection and Johne's disease (11)(12)(13)(14). Moreover, blockade of PD-1/PD-L1 and LAG-3/MHC-II binding with antagonist antibodies reactivated T-cell functions such as proliferation and cytokine production in vitro (11,(13)(14)(15)(16). However, expression of PD-1, LAG-3, and PD-L1 and their functions in cattle undergoing A. marginale infection have not been investigated.…”
mentioning
confidence: 99%
“…Insights into the chronic state or suppressed cellular responses have recently seen conflicting findings that Foxp3 is upregulated (Walsh, Brady, Finlay, Boon, & Mills, )but that anergic T‐cells, characterized by PD‐1, might have a bigger role to play. Recent evidence in ruminants suggest that γδ T‐cells, not CD4 T‐cells, are the major expresser of Foxp3 (Guzman et al., )and that immune checkpoint molecules such as PD‐1, CTLA‐4 and LAG1 might have greater roles to play in non‐responsive CD4 T‐cells during chronic infection (Ikebuchi et al., ). What has become apparent from a number of recent transcriptomic studies is that the il12 , tnf , and ifng complex is downregulated in ovine PBMCs as infection progresses (Fu et al., ), whilst within the liver, genes mediating Th2 cellular responses were upregulated (Alvarez Rojas et al., ).…”
Section: Immunity To Fasciola Sppmentioning
confidence: 99%